Hemodynamic response to ketamine in children with pulmonary hypertension. Issue 1 (13th November 2015) - Friesen, Robert H.; Twite, Mark D.; Nichols, Christopher S.; Cardwell, Kathryn A.; Pan, Zhaoxing; Darst, Jeffrey R.; Wilson, Neil; Fagan, Thomas E.; Miyamoto, Shelley D.; Ivy, D. Dunbar
Summary: Background: The safety of ketamine in children with pulmonary hypertension has been debated because of conflicting results of prior studies in which changes in mean pulmonary artery pressure (mPAP) and pulmonary vascular resistance (PVR) have been widely variable. The goal of this prospective study was to quantitate the effects of ketamine on pulmonary hemodynamics in a cohort of children with pulmonary hypertension under conditions in which variables such as airway/ventilatory management, FiO2, and use of vasodilating anesthetics were controlled. Methods: The IRB approved this study of 34 children undergoing cardiac catheterization for pulmonary hypertension studies. Following anesthetic induction with sevoflurane and tracheal intubation facilitated by the administration of rocuronium 0.7–1 mg·kg −1 iv, sevoflurane was discontinued and anesthesia was maintained with midazolam 0.1 mg·kg −1 iv (or 0.5 mg·kg −1 po preoperatively) and remifentanil iv infusion 0.5–0.7 mcg·kg −1 ·min −1 . Ventilation was mechanically controlled to maintain PaCO2 35–40 mmHg. When endtidal sevoflurane was 0% and FiO2 was 0.21, baseline heart rate (HR), mean arterial pressure (MAP), mPAP, right atrial pressure (RAP), pulmonary artery occlusion pressure (PAOP), right ventricular end‐diastolic pressure (RVEDP), cardiac output, and arterial blood gases were measured, and indexed systemic vascular resistance (SVRI), indexed pulmonary vascular resistance (PVRI), and cardiac index (CI) were calculated. Each child then received a bolus of ketamine 2 mg·kg −1 infused over 2 min. Measurements and calculations were repeated 2 min after the conclusion of the infusion. Results: The mean (95% CI) increase in mPAP following ketamine was 2 mmHg (0.2, 3.7), which was statistically significant but clinically insignificant. PVRI and PVRI/SVRI did not change significantly. Hemodynamic changes did not differ among subjects with differing severity of pulmonary hypertension or between subjects chronically treated with pulmonary vasodilators or not. Conclusion: Ketamine is associated with minimal, clinically insignificant hemodynamic changes in sedated, mechanically ventilated children with pulmonary hypertension. Abstract :